Prevalence of Diabetic Retinopathy in Patients with Cerebrovascular Accident: A Cross-sectional Study - (Col.) OK Radhakrishnan; Rutu K Rao; Varsha Manade; Swaranjali Gore; Shreya Gandhi; Khushboo Goyal; Tushar Agrawal (Journal of Clinical and Diagnostic Research)
Introduction: Diabetes Mellitus (DM) causes high blood sugar, leading to complications such as cerebrovascular events, chronic kidney disease, cardiovascular issues and retinopathy. Diabetic Retinopathy (DR) is a key microvascular complication and may indicate other diabetic issues. Studies suggest a link between DR and Cerebrovascular Accidents (CVAs) (strokes), particularly in low and middle-income countries where stroke rates are increasing. Aim: To assess the prevalence of DR among individuals who have experienced CVAs and to explore the relationship between DR and CVAs within the Indian population. Materials and Methods: The present cross-sectional study was conducted in the Department of Ophthalmology, Dr. D. Y. Patil Medical College and Research Centre (tertiary care hospital), Pimpri, Pune, Western Maharashtra, India, from November 2022 to June 2024. The study included 100 patients (200 eyes) aged 40-70 years with CVAs and diabetes. Details regarding age, gender and, detailed ocular and systemic information were recorded. Diagnosis of DM and CVA is done according to standard methods. Intraocular pressure was measured using the Goldmann Applanation Tonometer (GAT) and Optical Coherence Tomography (OCT). DR was classified based on severity into mild, moderate and severe groups. Data were analysed using Statistical Package for Social Sciences (SPSS) software version 26.0. Statistical significance was set at 5%. Results: In the present study, patients with DR had a mean±Standard Deviation (SD) age of 57.13±7.63 years. Among the CVA patients, 79% had DR. A total of 44 (44%) patients had moderate Non Proliferative Diabetic Retinopathy (NPDR), 20 (20%) had mild NPDR and 15 (15%) had severe NPDR. The average age of DR patients was 57.13±7.63 years, compared to 51.48±6.36 years for non DR patients. Haemorrhagic strokes were more common, occurring in 59 (59%) patients. Patients with both DR and CVAs were older and had higher blood sugar and HbA1c levels than those without DR. No association was found between DR and the type of stroke (p-value 0.761). Conclusion: Diabetic retinopathy was present in 79% of stroke patients, with moderate NPDR being the most common type. DR patients were older and had higher blood sugar and HbA1c levels. Haemorrhagic stroke was more prevalent in this group. However, no significant association was found between the types of stroke and DR.